Development of methods for the production of silicone membranes - Farmazyan, Z. M.; Atabekyan, M. L.; Hakobyan, E. H.; Hakobyan, R. M.; Grigoryan, S. G.; Topuzyan, V. O. («Գիտություն» հրատ.)
A simple method for the preparation of highly transparent hydrophobic thin silicone membranes using Floating-on-Water (FoW) technology has been proposed. The centrifugation method was also used to obtain homogeneous and transparent silicone membranes. A new approach to the one-step synthesis of Janus-type membranes has been proposed. Առաջարկվում է բարձր թափանցիկ հիդրոֆոբ բարակ սիլիկոնե թաղանթների արտադրության պարզ մեթոդ՝ օգտագործելով Floating-on-water (FoW) տեխնոլոգիան: Ցենտրիֆուգացման մեթոդը կիրառվել է նաև համասեռ և թափանցիկ սիլիկոնե թաղանթներ ստանալու համար։ Առաջարկվում է Յանուսի տիպի թաղանթների միաստիճան սինթեզի նոր մոտեցում։ Предложен простой способ изготовления высокопрозрачных гидрофобных тонких силиконовых мембран с использованием технологии Floating-on-Water (FoW). Для получения однородных и прозрачных силиконовых мембран исполь-зовался также метод центрифугирования. Предложен новый подход к одно-стадийному синтезу мембран типа Януса.
Keywords: Bioorganic chemistry; Organic chemistry